NLRP3 Is Involved in the Maintenance of Cerebral Pericytes - Quan, Wenqiang; Luo, Qinghua; Tang, Qiqiang; Furihata, Tomomi; Li, Dong; Fassbender, Klaus; Liu, Yang (Frontiers in Cellular Neuroscience, 2020)
Pericytes play a central role in regulating the structure and function of capillaries in the brain. However, molecular mechanisms that drive pericyte proliferation and differentiation are unclear. In our study, we immunostained NACHT, LRR and PYD domains-containing protein 3 (NLRP3)-deficient and wild-type littermate mice and observed that NLRP3 deficiency reduced platelet-derived growth factor receptor β (PDGFRβ)-positive pericytes and collagen type IV immunoreactive vasculature in the brain. In Western blot analysis, PDGFRβ and CD13 proteins in isolated cerebral microvessels from the NLRP3-deficient mouse brain were decreased. We further treated cultured pericytes with NLRP3 inhibitor, MCC950, and demonstrated that NLRP3 inhibition attenuated cell proliferation but did not induce apoptosis. NLRP3 inhibition also decreased protein levels of PDGFRβ and CD13 in cultured pericytes. On the contrary, treatments with IL-1β, the major product of NLRP3-contained inflammasome, increased protein levels of PDGFRβ, and CD13 in cultured cells. The alteration of PDGFRβ and CD13 protein levels were correlated with the phosphorylation of AKT. Inhibition of AKT reduced both protein markers and abolished the effect of IL-1β activation in cultured pericytes. Thus, NLRP3 activation might be essential to maintain pericytes in the healthy brain through phosphorylating AKT. The potential adverse effects on the cerebral vascular pericytes should be considered in clinical therapies with NLRP3 inhibitors.